Propagande catholique et littérature populaire : l’Église face aux défis de la question sociale (1876-1902) - Solange Hibbs (Cahiers de Civilisation Espagnole Contemporaine)
During the nineteenth century and the first decades of the twentieth century, the Spanish Catholic Church, encouraged by the Pope Leo xiii encyclicals and the six National Catholic Assemblies which took place from 1889 to 1903, sustained an offensive strategy of rechristianization of the civil society. In order to do so, the Catholic Spanish Church benefited from the freedom of expression and association implemented after the sexenio. With the support of Catholic laymen and the clergy, the Spanish Church coordinated multifaceted initiatives so as to intensify catholic propaganda.